Razlika med mesečnimi koeficienti padavin in odtoka kot metoda členitve rečnih režimov v Sloveniji - Gams, Ivan (Geografski vestnik, 1998)
Based on conclusions obtained from a detailed water balance for the Ščavnica drainage area, the simplified method is presented (for the use at smaller drainage areas in Slovenia), of analysing the origins of river water on the basis of comparing the monthly precipitation modules at the representative station with the river runoff modules. By applying this method at 19 cases a division was made, of year to months with the prevailing influence of rain, snow cover, evapotranspiration and the influence of groundwater as the modifiers of river regimes.
Keywords: odvodnjavanje; padavine; rečni režim; reke; Slovenia; Slovenija; vodna bilanca; vodni režim